2020
DOI: 10.2196/16281
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Health Information–Seeking Behavior of Students Aged 12 to 14 Years: Mixed Methods Study

Abstract: Background Many children and adolescents are surrounded by smartphones, tablets, and computers and know how to search the internet for almost any information. However, very few of them know how to select proper information from reliable sources. This can become a problem when health issues are concerned, where it is vital to identify incorrect or misleading information. The competence to critically evaluate digital information on health issues is of increasing importance for adolescents. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 35 publications
3
35
0
3
Order By: Relevance
“…eHEALS responses were quantitatively analysed to calculate an average score for each participant and an average score for the cohort. We followed other studies with similar target populations [ 30 ] and considered eHEALS scores above 3.5 out of 5 to represent high digital health literacy. Video recordings were analysed using an observational checklist based on previous research [ 34 ] (Additional file 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…eHEALS responses were quantitatively analysed to calculate an average score for each participant and an average score for the cohort. We followed other studies with similar target populations [ 30 ] and considered eHEALS scores above 3.5 out of 5 to represent high digital health literacy. Video recordings were analysed using an observational checklist based on previous research [ 34 ] (Additional file 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Self-efficacy explains that health behaviours are sustained when a person believes they are capable of executing a desired behaviour, for example via performance attainment when past success informs current behaviour [ 28 ]. Self-efficacy is useful for understanding adolescents’ digital health literacy capabilities [ 29 , 30 ]. It explains adolescents’ information-seeking motivation, behaviour and awareness of appraisal and application skills.…”
Section: Introductionmentioning
confidence: 99%
“…Internet and health literacy are fundamental facilities to improve medical student ISB (Gedefaw, 2020). Most of the students improve their health literacy search skill in workshop (Maitz et al , 2020). Health literacy is a basic skill to make success health-related decisions (Yamashita et al , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, several studies suggested that they often do not take into account or are not able to evaluate the reliability and credibility of the sources of the information they are presented with online (Hautala et al, 2018). For ADOLESCENTS ONLINE ACTIVE LEARNING 5 instance, Maitz et al (2020) found that more than 90% of the web pages visited by 14-year-olds during a health search task (i.e., suggest whether to get rid of a hairy mole) were judged poor or unreliable by independent raters. In particular, adolescents seem to fail to consider those aspects of the websites that would be relevant to appraise their reliability, such as the presence of advertisements (Gossen et al, 2011;McGrew et al, 2018), and do not take into account the website's sponsors or political and industry affiliations (McGrew et al, 2018).…”
Section: Efficiency In Identifying Appropriate Sources Of Informationmentioning
confidence: 99%
“…In particular, adolescents seem to fail to consider those aspects of the websites that would be relevant to appraise their reliability, such as the presence of advertisements (Gossen et al, 2011;McGrew et al, 2018), and do not take into account the website's sponsors or political and industry affiliations (McGrew et al, 2018). Instead, they often focus on more superficial cues, such as the vaunted expertise of the person providing information (e.g., the source of health-related information claiming to be a doctor, Maitz et al, 2020), or the website appearance (Freeman et al, 2018). In this respect, a meta-analysis by Dresang (2005) indicated that young people tend to discard the information coming from text-only websites, preferring more interactive pages, rich with video and visual content.…”
Section: Efficiency In Identifying Appropriate Sources Of Informationmentioning
confidence: 99%